Exploring the Philosophy of Time in Physics Education: Implications for Teaching Relativity and Quantum Mechanics - Firnando, Hero Gefthi (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2025)
This study examines the role of the philosophy of time in physics education, with particular focus on its implications for teaching relativity and quantum mechanics. Time is a fundamental yet perplexing concept in both theories, often posing challenges for educators and learners due to its abstract and counterintuitive nature. To address this, the research explores how philosophical perspectives on time can inform and improve teaching practices. A qualitative approach was employed, consisting of a systematic literature review of both philosophy of physics and physics education research, combined with a textual and pedagogical analysis of existing teaching strategies used in relativity and quantum mechanics instruction. Sources included peer-reviewed journals, educational frameworks, and documented classroom practices. Data were organized and coded using NVivo software to identify recurring themes in how philosophical engagement with time has been integrated into teaching. The findings indicate that incorporating structured philosophical discussions—such as debates on the nature of simultaneity or the problem of temporal measurement in quantum mechanics—can clarify conceptual paradoxes and provide students with alternative interpretive frameworks. Evidence of improved comprehension was drawn from reported student reflections, documented learning outcomes, and thematic patterns in prior classroom-based studies, rather than self-reported claims alone. Furthermore, the integration of philosophy was shown to foster critical thinking, operationalized here as students’ ability to question assumptions, articulate multiple interpretations, and resolve conceptual tensions in physics discourse. The study concludes that systematically embedding the philosophy of time into the physics curriculum can significantly enhance comprehension of relativistic and quantum principles, refine teaching methodologies, and cultivate a more reflective and critical learning environment.